A Quasi Experimental study to Compare Thermo-regulator blanket with conventional method (incubator) for temperature regulations in preterm, Low Birth weight neonates landing at Emergency department of a tertiary care pediatric facility - Gowa, Murtaza Ali; Rakhia, Allah; Bozdar, Muhammad Hayat; Mehboob Noonari; Raza, Syed Jamal (Journal of the Pakistan Medical Association, 2022)
Objective: To compare incubator and thermal blanket for thermoregulation in preterm and low birth weight neonates. Method: The pilot study was conducted from January to March 2018 at the emergency department of the National Institute of Child Health, Karachi, and comprised preterm and low birth weight neonates without any co-morbidity who were randomised to control and interventional groups. Data was collected using a proforma about demographics, weight, gestational age and brief clinical history. Temperature, blood pressure and pulse were monitored along with other routine care after every 15 minutes in the incubator, and the same procedure was adopted for thermal blankets. Data was analysed using Statistical Package for Social Sciences (SPSS) Version 23. Results: Of the 38 subjects, 19(50%) each were cases and controls. The mean gestational age between the groups was not significantly different (p>0.05). Temperature for the first 60 minutes remained similar in the two groups, but at 75 minutes and onwards, the incubator showed a significantly better results (p<0.05). Conclusion: Thermal blankets can sufficiently provide a hyperthermic environment to the neonates, but an incubator is a more reliable option to provide sustained temperature. Key Words: Incubators, Thermoregulation, Infants, Neonates, Preterm, Low birth weight, Thermoregulator blankets.